The Digital Economy and Its Impact on International Trade - Mhd Rizki Dermawan (Journal of Economics, Management, Development, and Education, 2026)
The digital economy accelerates global trade, opening access for MSMEs, but poses challenges such as digital inequality and regulation. Technology investment and policy harmonization are necessary for inclusive trade. This paper aims to analyze the impact of the digital economy on international trade, including opportunities, challenges, and the role of regulation in supporting inclusive and sustainable trade. The research method used is qualitative with a descriptive approach. The results of this paper indicate that the digital economy has brought significant changes to international trade by increasing efficiency, market access, and reducing transaction barriers. However, the benefits have not been felt evenly, especially in developing countries that still face infrastructure and technological literacy constraints. Adaptive regulation and investment in digital infrastructure are key to ensuring inclusive and sustainable digital trade. International cooperation is needed to create a fairer trade ecosystem, where every country has an equal opportunity to thrive in the digital economy. With the right strategy, the digital economy can become a key driver of more equitable and sustainable global economic growth.